CREB–KIF1A–CGRP-positive feedback loop drives central sensitization in chronic migraine - Wei Jiang; Peng Yu; Yan-Min Shi; Li-Xi Zhang; Meng-Tan Cai; Yu Yang; Ming Dong (The Journal of Headache and Pain, 2025)
Abstract Background Chronic migraine (CM), defined as ≥ 15 monthly headache days and often involving central sensitization, is a complex neurological disorder. While calcitonin gene-related peptide (CGRP) is a key migraine target, its upstream regulation remains unclear. Kinesin family member 1A (KIF1A), which is essential for axonal transport, is transcriptionally regulated by cAMP response element-binding protein (CREB). The aim of this study was to elucidate the role of the CREB–KIF1A–CGRP signaling axis in the pathogenesis of migraine. Methods CMs were generated in mice through repeated nitroglycerin (NTG) injections, and thermal and mechanical allodynia was evaluated behaviorally. Molecular changes in the spinal trigeminal nucleus caudalis (SP5C) and Neuro-2a cells were examined using immunoblotting, qPCR, and immunofluorescence. Mechanistic studies included chromatin immunoprecipitation and dual-luciferase assays to verify the CREB-mediated transcriptional regulation of Kif1a, coimmunoprecipitation (Co-IP) to assess KIF1A–CGRP interactions, and synaptosomal CGRP analysis following Kif1a knockdown. Pharmacological interventions included Forskolin (a CREB agonist), 666 − 15 (a CREB inhibitor), Kif1a knockdown/overexpression, and Olcegepant (a CGRP receptor antagonist). Results NTG treatment activated the CREB–KIF1A–CGRP pathway and induced migraine-like hypersensitivity. Forskolin-induced CREB activation upregulated KIF1A and CGRP expression, whereas inhibition of CREB expression by 666 − 15 reversed these effects. ChIP and luciferase assays confirmed the direct binding of CREB to the Kif1a promoter. Kif1a knockdown reduced p-CREB, CGRP, and c-Fos levels in SP5C tissue and Neuro-2a cells, alleviating behavioral hypersensitivity. Co-IP showed that KIF1A physically associated with CGRP, and synaptosome analysis revealed decreased CGRP in vesicles after Kif1a knockdown. Overexpression of Kif1a increased CGRP levels, but this effect was reversed by age. CGRP receptor blockade also inhibited Forskolin-induced activation of p-CREB, c-Fos, and KIF1A. These findings support a CGRP-dependent positive feedback loop within the CREB–KIF1A–CGRP axis that drives migraine pathogenesis. Conclusions These findings reveal a CREB–KIF1A–CGRP positive feedback loop that drives migraine-like hypersensitivity. CREB directly regulates KIF1A transcription, which in turn promotes CGRP expression and signaling. Disruption of this axis effectively attenuated migraine-associated behaviors and molecular responses, highlighting potential therapeutic targets for the treatment of CM. Graphical abstract